The value of aesthetic judgements in athletic performance - Toner, J.; Montero, B. (The Journal of Somaesthetics, 2020)
A considerable volume of research has explored spectators` attraction to the aesthetic aspects of sport. However, considerably less attention has been devoted to an evaluation of the aesthetic dimension of sport from the performer`s perspective. We hypothesize that such evaluation can benefit athletic skill, and in the current paper substantiate and elucidate some of the types of aesthetic experiences athletes may undergo and consider their potential use in sports. We see this work as propaedeutic to future empirical work investigating the role of aesthetic selfevaluation in athletic performance.